Methylenetetrahydrofolate reductase polymorphism and pre-eclampsia. Issue 6 (June 1997) - Sohda, S; Arinami, T; Hamada, H; Yamada, N; Hamaguchi, H; Kubo, T
Abstract : A common missense mutation in the methylenetetrahydrofolate reductase (MTHFR) gene, a C to T substitution at nucleotide 677, is responsible for reduced MTHFR activity and associated with modestly increased plasma homocysteine concentrations. Since underlying maternal vascular disease increases the risk of pre-eclampsia, we had the working hypothesis that pre-eclampsia patients would have an increased T677 allele frequency compared with controls. The MTHFR genotypes were determined in 67 pre-eclampsia patients, 98 normal pregnant women, and 260 healthy adults by the PCR/RFLP method. The T677 allele and the genotype homozygous for the T677 allele were significantly increased in the pre-eclamptic group compared with the controls (p < 0.02 and p < 0.004, respectively). The data indicate that the T677 variant of the MTHFR gene is one of the genetic risk factors for pre-eclampsia.